POST WEANING FEEDING MANAGEMENT AND PERFORMANCE OF MERINO EWES GRAZING ON NATURAL AND IMPROVED PASTURES AT MATING SEASON - Bianchi,Gianni (2001)
In the uruguayan Basalt region, the reproductive performance of 300 Merino ewes and the effect of 3 post-weaning feeding managements (PWFM: I: 1.2 cm height of available forage and 16 ewes/ha; II: 2.03 cm height of available forage and 5 ewes/ha; III: 2.5cm height of available forage and 1 ewe/ha) as well as 2 feeding levels before and during the breeding season (FLM: native pastures: green DM/ha: 883kg, CP: 114g/kg DM, NDF: 781g/kg DM and improved pastures: DM /ha: 1270kg, CP: 194g/kg DM, NDF: 598g/kg DM) were studied with a factorial arrangement of treatments. The PWFM extended for 70 days, ewes were mated in the period from 13/4/96 to 13/5/96 and FLM were applied for 30 days, starting 15 days before beginning of breeding. There were not differences on the ovulation rate (P>0.05); however, the P values might indicate some effect of the treatments. The number of born lambs/ewe served increased with the ovulation rate because the higher number of ovulations balanced their less viability, individually considered. Actually, the number of born lambs/ewe served was higher with animals coming from PWFM III (1.18, 1.11 and 0.96, PWFM III, II and I, respectively; P = 0.02) and with the animals grazing on improved pastures at mating period (1.13 and 1.03, improved pastures and natural pastures, respectively; P = 0.10), were those which showed slight higher ovulation rate.